Piriformospora indica augments arsenic tolerance in rice (Oryza sativa) by immobilizing arsenic in roots and improving iron translocation to shoots - Ghorbani, Abazar; Tafteh, Mahdi; Roudbari, Nasim; Pishkar, Leila; Zhang, Wenying; Wu, Chu (Ecotoxicology and environmental safety, 2021)
Arsenic (As) toxicity can be a hazardous threat to sustainable agriculture and human health. Piriformospora indica (P. indica), as a beneficial endophytic fungus, is involved in the plant tolerance to stressful conditions. Here, the biochemical and molecular responses of rice plants to As (50 μM) phytotoxicity and P. indica inoculation as well as the role of P. indica in improving rice adaptation to As stress were evaluated. The results showed that As stress reduced chlorophylls content, chlorophyll fluorescence yield (Fv/Fm), electron transport rate (ETR) and growth. However, P. indica restored chlorophyll content and growth. P. indica decreased the contents of methylglyoxal and malondialdehyde by improving the activity of enzymes involved in the glyoxalase pathway and modulating the redox state of the ascorbic acid-glutathione cycle, and consequently, increased the plant tolerance to As toxicity. P. indica, by downregulating Lsi2 expression (involved in As translocation to the shoot) and upregulating PCS1 and PCS2 expression (involved in As sequestration in vacuoles), immobilized As in the roots and reduced damage to photosynthetic organs. P. indica increased iron (Fe) accumulation in the shoot under As toxicity by upregulating the expression of IRO2, YSL2 and FRDL1 genes. The results of the present study augmented our knowledge in using P. indica symbiosis in improving the tolerance of rice plants against As toxicity for sustainable agriculture. [Display omitted] •P. indica improved photosynthetic pigments and the efficiency of photosynthetic apparatus of rice plants under As toxicity.•P. indica reduced MDA and MG levels by modulating AsA-GSH homeostasis, as well as the glyoxalase system.•P. indica reduced As accumulation in shoot by downregulating the expression of Lsi2, Lsi6, Nramp1 and Nramp5.•P. indica increased Fe translocation to shoots by modulating the expression of IRO2, FRDL1 and YSL1 genes.•P. indica sequestrated As in the roots by upregulating the expression of PCS1 and PCS2 genes.